Методика вибору оптимальної марки ніздрюватого бетону для стін - Пашинський, В. А.; Карпушин, С. О.; Pashinsky, V.; Karpushyn, S. (ОДАБА, 2017)
Одним з ефективних стінових матеріалів є ніздрюватий бетон, показники міцності та теплопровідності якого можуть змінюватися в досить широкому діапазоні залежно від марки за середньою густиною. Розроблена методика вибору оптимальної марки ніздрюватого бетону базується на вирівнюванні товщин стіни, необхідних за умовами теплового захисту та несучої здатності. Встановлені наближені аналітичні залежності коефіцієнта теплопровідності та розрахункового опору від середньої густини ніздрюватого бетону та запропонована спрощена методика оцінювання несучої здатності простінка з урахуванням геометричних параметрів будівлі, навантажень від ваги конструкцій та корисних навантажень на перекриття. Розроблена методика проілюстрована прикладами розрахунку. One of the most effective wall materials are porous concrete indicators of strength and thermal conductors that can change in wide range, depending on the brand of an average density. By increasing of an average density, increases the average of thermal conductivity and wall thickness, that is required in terms of thermal protection. Simultanlously increases the strength and decreases the thickness of the walls due to carring capacity. The technique of choosing the optimal brand of porous concrete, bases on aligning wall thickness, required in terms of thermal protection and carring capacity. Object of study are exterior bearing walls that are typical for low-rise residential and public buildings. To solve the optimizational problem set an approximate analitycal dependence of thermal conductivity and calculated resistance of average density porous concrete. Bearing capacity of the pier in safety margin, estimated by the strength criteria considering the geomatric building options, loads of weight structures and payloads on the ceiling. The basis for selection the optimal brand of a porous concrete are the wall thickness, that is required to satisfy conditions of the bearing capacity and thermal insulation of medium density. The equality of thickness, determines the optimal brand of porous concrete of an average density. Calculation samples showed that for eraction 2…3 storaged public building, a porous concrete brand D 400…D 500 should be used.
The methodology of optimal choise of the brand of aerated concrete for walls
Keywords: стіни будівель; ніздрюватий бетон; марка за середньою густиною; building walls; porous concrete an average; density mark